Experimental investigations of the performance of a flat-plate solar collector using carbon and metal oxides based nanofluids. (15th July 2021) - Akram, Naveed; Montazer, Elham; Kazi, S.N.; Soudagar, Manzoore Elahi M.; Ahmed, Waqar; Zubir, Mohd Nashrul Mohd; Afzal, Asif; Muhammad, Mohd Ridha; Ali, Hafiz Muhammad; Márquez, Fausto Pedro García; Sarsam, Wail Sami
Abstract: Covalently functionalized carbon nanoplatelets and non-covalent functionalized metal oxides nanoparticles (surfactant-treated) have been used to synthesize water-based nanofluids in this paper. To prove nanofluid stability, ultraviolet–visible (UV–vis) spectroscopy is used, and the results show that nanofluid is stable for sixty days for carbon and thirty days for metal oxides. The thermophysical properties are evaluated experimentally and validated with theoretical models. Thermal conductivities of f-GNPs, SiO2, and ZnO nanofluids are enhanced by 25.68%, 11.49%, and 15.42%, respectively. Lu-Li and Bruggeman's thermal conductivity models are correctly matched with the experimental data. Similarly, the viscosity, density, and specific heat capacity of nanofluids are measured and compared with theoretical models. The enhancement in density, specific heat and viscosity of f-GNPs, ZnO, and SiO2 nanofluids are 0.12%, 0.22%, and 0.12%; 1.54%, 0.96%, and 0.73%; 12%, 9.41%, and 24.05% respectively in comparison of distilled water. A flat-plate solar collector is installed, and its thermal performance is evaluated by using carbon and metal oxides based nanofluids, following the ASHRAE standard 93–2003, at different heat flux intensities (597, 775, and 988 W/m 2 ), mass flow rates (0.8, 1.2 and 1.6 kg/min), inlet fluid temperatures (30–50 °C) and the weight concentrations (0.025–0.2%). The thermal efficiency of the flat-plate solar collector is measured for distilled water and compared with the weight concentration (0.025–0.2%) of functionalized carbon and metal oxide-based nanofluids. A comparison of 0.1 wt% water-based nanofluids can be sequenced f-GNPs > ZnO > SiO2 because of a percentage improvement of thermal efficiency of the flat-plate solar collector obtained at a mass flow rate of 1.6 kg/min with values of 17.45% > 13.05% > 12.36%, respectively in comparison to water. Highlights: Covalent and non-covalent functionalization of graphene & metal oxides nanoparticles. Thermophysical was evaluated, and 25.68% improved thermal conductivity was reported for f-GNPs. The solar flat plate collector's thermal performance was improved by 17.45% for f-GNPs compared to DI water.